A CFD Energetic study of the influence of the panel orientation in Open Joint Ventilated Façades - M.J. Suárez; M.N. Sánchez; E. Blanco; M.J. Jiménez; E. Giancola (Energy Reports, 2022)
The arrangement of the panels in Open Joint Ventilated Façades (OJVF) is a potential factor in improving the energy efficiency of this building system. The distribution of joints in the façade influences the behaviour of the air flow in the channel which in turn could affect the overall heat exchanges with the envelope and thus the internal conditions of the building. Tiling panels can be installed on ventilated façades with different arrangement patterns according to the layout of the joints: lined up, staggered, stepped, diagonal or random, although manufacturers recommend a façade layout with in-line gaps to avoid costly façade maintenance. Thus, landscape and portrait layout with continuous joints are the most frequent arrangement in ventilated façades. This research assesses the benefit of the installation of OJVF panels in both layouts in order to reduce the cooling loads. Two real OJVFs with different panel arrangements, landscape and portrait, are analysed. Also, they are compared with a conventional façade with a sealed air cavity. All solutions are modelled and simulated using the commercial computational fluid dynamics software ANSYS FLUENT to evaluate the fluid-dynamic and thermal behaviour of the façades in summer and winter conditions. The energy performance of these solutions is evaluated, analysing different parameters such as panel’s temperature, mean air velocity inside the cavity, fluid pathlines through the open joints and thermal flux in the air cavity and to the room. The airflow inside the cavity is mainly driven by thermal buoyancy in all façades but differs from bi-dimensional convective loops in conventional façades to three-dimensional complex and asymmetrical airflows in OJVFs. The results obtained show that both OJVF configurations perform much better than the conventional sealed façade, reducing the heat transfer into the room by 30% in the summer period. In any case, the landscape OJVF façade reduces the transfer in the same period to a minimum value of 7.3 W/m2, which is 3% less than the flux transferred through the vertical one. This small difference in the energy performance of OJVFs makes the choice of panel orientation more based on other criteria such as aesthetics.